Job satisfaction and performance: A survey study on internship students of Universitas Negeri Malang - Rosyidah Rosyidah; Utami Widiati; Andika Agung Sutrisno; Ary Fauzi; Kukuh Prayitno Subagyo; Nurhidayati Nurhidayati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to describe the satisfaction of host companies to internship students toward their competencies and performance and suggest improvements to the internship program. The research subjects were students who were undertaking internships in 64 institutions in Malang areas, both in the business and industrial world. Research data are obtained from questionnaires. The results showed that the qualifications of the internship students were in the range of good to very good. These findings are following the expectations of host companies, which also recognize that the competencies of internship students are in line with their expectations and needs. However, some students worked less efficiently, so host companies are not really satisfied. According to the host companies, three things need to be improved: (1) the duration of the internship, (2) monitoring, and (3) student readiness. Regarding the length of the internship, host companies suggest that the internship program's duration occupies at least three months. Host companies hope that the supervisors monitor all students who are apprenticed. Besides, the internship students should prepare in advance by giving them special provisions about the company's product knowledge and related hard skills and soft skills needed in the future jobs. These findings suggest the universities, faculties, students, host companies to develop both of the experiences and satisfaction as possible.